Evaluation of clopidogrel, hypercoagulability, and platelet count in dogs undergoing splenectomy for splenic masses - Guk-Il Joung; Jeong-Yeol Bae; Jung-Il Kim; Jin-Young Kim; Joong-Hyun Song (Veterinary Quarterly, 2024)
Dogs that had splenectomy are predisposed to fatal thrombotic conditions, and thrombocytosis is a risk factor for post-splenectomy hypercoagulability. However, in veterinary medicine, there are no specific therapeutic approaches for managing this hypercoagulability. This study aimed to determine the preventive effect of clopidogrel on post-operative hypercoagulability during the first 2 weeks post-splenectomy in dogs with splenic masses. This study included 12 dogs that had splenectomy. Seven dogs received no treatment (group A), and five were treated with clopidogrel (group B). Clopidogrel was loaded at 10 mg/kg on day 2 and continued at 2 mg/kg until day 14. Blood samples were collected on the day of surgery and 2, 7, and 14 days after splenectomy in both groups. In group B, thromboelastography (TEG) was performed on the same days. In group A, there was significant elevation of platelet counts on days 7 (p = 0.007) and 14 (p = 0.001) compared to day 0. In group B, the platelet counts were significantly elevated on day 7 (p = 0.032) but no significant difference was found on day 14 compared to day 0. Platelet counts on day 14 were significantly higher in group A than in group B (p = 0.03). The lower platelet counts were correlated with alterations in TEG parameters, and no significant differences were found in the K and α-angle values at all postoperative assessment points compared to day 0. Our study suggests that clopidogrel may reduce post-operative thrombocytosis and hypercoagulability in dogs that undergo splenectomy for splenic masses.